Competency Based Assessment Techniques at MAS Ishlahiyah Binjai - Nabila, Nabila; Delima, Septia Putri; Ala, Nurul; Nurmalasari, Nurmalasari; Nuriyani, Nuriyani (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research explores the development of competency-based teacher performance assessment methods to improve the quality of higher education. Using a comprehensive literature study methodology, this research explores the basic concept of competency in the context of higher education, analyzes existing teacher performance assessment methods, and identifies obstacles and challenges in the assessment process. Key findings include an in-depth understanding of the essential competencies expected of higher education teachers, an exploration of existing assessment methods, and a critical analysis of barriers such as subjectivity and resistance to change. This research culminates in formulating a robust conceptual framework for competency-based assessment methods. The implications of the research suggest that the proposed assessment method, with its focus on critical aspects of teaching, has the potential to significantly improve the quality of higher education. The results of the research are competency-based assessment instrument products for web programming practicum in the form of practical competency-based tests, practical competency assessment rubrics and affective aspect assessment rubrics. The development results meet validity requirements, based on expert assessments which are analyzed using the Aiken index coefficient. The practicality of the product is also fulfilled through the very positive response given by teachers as users and the teacher's ability category is very good. Student learning outcomes that exceed the KKM show that the product developed meets the effective criteria